The Impact of Inflation on Zakah - Firmansyah Firmansyah; Aas Nurasyiah; Muhammad Kamal Muzakki; Romi Hardiansyah (Review of Islamic Economics and Finance, 2021)
AbstractPurpose - This paper aims to reveal how the impact of inflation on zakah can reduce the actual value of zakah collected, study the fiqh about zakah distribution, and apply zakah fund reserves funds not distributed entirely.Methodology - The method used is qualitative with the form of library research (library research). This paper concludes that inflation impacts zakah acceptance; that is, the amount of zakah collected is reduced. The management of zakah by the state in some of the scholars’ reviews turns out to have a more significant positive impact than if zakah is distributed individually by muzaki.Findings - The rule regarding zakah funds reserves, in distributing zakah during the time of the Prophet ﷺ is never to delay the distribution of zakah, the zakah received is then distributed to the asnaf, so that the nature of zakah distribution during the time of the Prophet ﷺ is immediately and distributed without remainder.Keywords: Inflation, Zakah, Zakah Funds Reserves.